Pagar Nusa Endeavors to Knitting Towards a Moderate Society - Muliadi, Muliadi; Gojali, Muhtar; Wasik, Abdul; Maulani, Maulani (Letiges, 2023)
This study examines the role of Pagar Nusa, an autonomous body of Nahdlatul Ulama (NU) in Indonesian traditional martial arts, in realizing a moderate society. Pagar Nusa is dedicated to exploring, developing and preserving the Nahdlatul Ulama martial art, which has deep spiritual and cultural values. This study uses a field approach, including a type of qualitative research. Data was obtained through observation, interviews and documentation to explore the programs implemented by Pagar Nusa in fostering moderation. Data analysis techniques are processed, presented, and inference or validation. Through training, competitions and seminars, Pagar Nusa aims to introduce pencak silat to the broader community and educate the younger generation about the importance of cultural heritage and ethical self-defence skills. This study emphasizes the principles of religious moderation, such as balance, justice, kindness, and wisdom, which form the basis of Pagar Nusa's activities. The findings of this research contribute to the understanding of how pencak silat can be an effective instrument in promoting moderation and fighting radicalism in a multicultural society which ultimately encourages positive social change.